Virtual museums: interpreting and recreating digital cultural content. - Bovcon, Narvika (Neohelicon, 2021)
The use of digital information technologies in the humanities, and the various new-media art projects, presents a plethora of opportunities for the archiving of the digitized/digital cultural content, such as online databases and virtual museums. On the other hand, the digital archives are never something permanent, they are vulnerable as regards the maintenance and also the technological development in general, which makes software and hardware obsolete after only a few years. The paper reflects on both issues by considering the case studies of visualizing a literary-history database and of translating new-media art exhibitions from the real gallery space into a virtual museum presentation. The ephemeral character of conceptual art and the artistic approaches to archiving of art are scrutinized in the writings and works of Marcel Duchamp, providing us with relevant models for dealing with maintenance and obsoleteness issues of archiving also in the contemporary new-media art and its presentations. The strategies of recreation and reinterpretation of past art works for contemporary audiences, and their integration into new artistic explorations of artists and students, are suggested as forms of preserving of cultural heritage.